Pengabdian Kepada Masyarakat; Pelayanan Bimbingan Pendidikan Keluarga dan Pendidikan Anak Usia Dini di Desa Sekaroh Lombok Timur - Zinnurain Zinnurain; Jessica Festy Maharani; M Najamuddin (Fakultas Ilmu Pendidikan dan Psikologi, 2023)
AbstractThe purpose of the program is as an effort to provide services to parents and early childhood in Sekaroh village in order to get the opportunity to learn briefly about family education and early childhood education through community service activities; Family Education and Early Childhood Education Guidance Services in Sekaroh Village, East Lombok. The method used in community service activities (PKM) is the lecturing and drill method. The activity was carried out in Sekaroh Village, Jerowaru District, East Lombok Regency. This activity is carried out during the second semester period of the 2022/2023 academic year. This activity lasted for 1 month from 8 May to 5 June 2023. The collecting data instrument used was an interview questionnaire with interview subjects namely parents and children. The results of the activity show that in stage 1 the evaluation results showed an increase in understanding based on the results of a questionnaire filled in as much as 45% of parents and children understood the material presented and succeeded in completing the activities given by the team but with the